Результати комп’ютерного моделювання процесу формування литого поршню для двигунів внутрішнього згоряння - Пуляєв, Антон Анатолійович; Золотарева, Анастасія Вадимівна; Чумаченко, Віталій Іванович; Богдан, Вікторія Володимірівна; Бєлік, Микола Миколайович (НТУ "ХПІ", 2016)
Проведено комп’ютерне моделювання процесів заповнення кокілю розплавом при виготовленні литих поршнів двигунів внутрішнього згоряння (ДВЗ). На основі аналізу динаміки охолодження виливки, фазового переходу, пов'язаності зон, що кристалізуються в останню чергу, виявлено зони формування внутрішніх дефектів, зокрема газової та усадкової пористості. Запропоновано використання результатів моделювання процесів заповнення робочої порожнини кокілю для подальшої параметричної класифікації з визначення проблемних зон у виливках поршню.

The actual applied problem of development of design and technological solutions for the manufacture of internal combustion engine (ICE) pistons is studied. A computer simulation of the processes of chill filling with a melt is carried out. Based on the analysis of the cooling dynamics of the casting, the phase transition and the bonding of the zones crystallized last of all, zones of formation of internal defects, in particular, gas and shrinkage porosity, are identified. The use of the simulation results of the filling processes of the chill mold working cavity for further parametric classification by determination of problem zones in piston castings is proposed. A comprehensive approach to design and technological solutions, as well as a procedure for determining the localization of internal defects cast by an ICE piston, is proposed. In particular, parametric methods of classification are proposed, which can be performed on the basis of the results of computer simulation of the filling process of the chill mold working cavity.
A computer simulation FORMATION of cast pistons for internal combustion engines
Keywords: ДВЗ; кокіль; газова пористість; усадкова пористість; chill mold; gas porosity; shrinkage porosity